Características atuais associadas à história de aborto provocado Current characteristics associated with the history of induced abortion - Ellen Hardy; Rosely G. Costa; Telma Rodrigues; Teresinha M. de Moraes (Universidade de São Paulo, 1994)
Com o objetivo de analisar a associação de algumas características sociodemográficas atuais com o fato de ter realizado ou não um aborto, foram estudadas 138 alunas de uma universidade brasileira, que haviam tido pelo menos uma gravidez. Essas alunas foram identificadas dentre as 937 que devolveram, pelo correio, questionário auto-respondido, anonimamente, distribuído a todas as alunas da graduação. As alunas foram divididas em dois grupos, segundo tenham feito pelo menos um aborto ou não. Constatou-se que a maior proporção de mulheres que havia abortado esteve entre aquelas com até 24 anos de idade, sem companheiro, sem religião e sem nenhum filho vivo por ocasião do estudo. A análise por regressão logística apontou não ter filhos vivos como característica atual associada à realização de um aborto. For the purpose of analysing the association between selected current socio-demographic characteristics and the history of induced abortion, 138 students of a Brazilian university, who had been pregnant at least once, were studied. These students were identified from among the 937 who returned, by mail, a self-administered, anonimous questionnaire distributed to all the femele undergraduates. The subjects were divided into two groups, those who had and those who did not have a history of induced abortion. It was found that the largest percentage of women who had already had an induced abortion were of less than 24 years of age, were not living in marital union, had no religious affiliation and no living children at the time of the study. Analysis by logistic regression showed that having no living children was the only current characteristic associated with having had an induced abortion.